KAJI TINDAK PENINGKATAN EFEKTIVITAS KOMUNIKASI VERBAL PENYULUH LAPANGAN PERTANIAN (PPL) DI KABUPATEN SUKOHARJO - Suminah Suminah; Emy Widiyanti; Bekti Wahyu Utami (AGRITEXTS: Journal of Agricultural Extension, 2004)
This research is aimed studied duty execution Counselling of Pertanian in field and studying relation to acting communications, analysing activity which and create appliance assist or relevant counselling media. An underlying method employed in the research is a analytical descriptive method wit explanatory strategy, topical, Focuss Grup Discussion (FGD) and formulation of model. The result of research shows that agriculture extension agent in executing duty accustomed use counselling media which in the form of leaflet and poster. Farmer majority express items understanding will which is given so that they often apply felt items as according to requirement. Effort to increase communications affectiveness is to through small discussion and extension agent uplifting of skill. While appliance and method assist matching with condition local society is meeting or discourse by means of appliance assist leaflet.